Zapatismo en México y la CONAIE en Ecuador: Convergencias y divergencias de dos modelos de resistencia contrahegemónica-étnica - López Oropeza, Mauricio (Nómadas. Critical Journal of Social and Juridical Science, 2010)
This reflection intends to recover relevant interpretative hints which would allow us to find new ways to understand the complex, ongoing and still building up of the “Zapatista” movement and resistance in Mexico, going back to its deep historic background, so we can reinterpret its impact, transformations, and above all, its ethnic grassroots, contrasting it with the indigenous movement in Ecuador, mainly through its organizational structure: the “CONAIE” Confederation of Indigenous nationalities in Ecuador. Reading their historic parallelism and shared visions coming from centuries of exclusion as excluded and abused communities, which experienced the consequences of the Neoliberal economic and cultural societal structure through the Structural Adjustment Plans implemented by the rich countries and its counter-parts politicians and industrial elites in Mexico and Ecuador. While deepening on the Zapatista movement in Southern Mexico, we will establish the convergences and divergences with the indigenous movement in Ecuador, trying to link their positions to transform the unjust social, economical, cultural and political structures, using their ethnic roots as a platform for the emergence of new indigenous leaderships in both cases, changing the scenery for the Non Governmental Organizations and the so called “Civil Society” both in Mexico and in Ecuador.